Improving Eight-State Continuous Variable Quantum Key Distribution by Applying Photon Subtraction - Qingquan Peng; Xiaodong Wu; Ying Guo (Applied Sciences, 2019)
We propose a new method to effectively improve the performance of a quantum key distribution with eight-state continuous variables by the photon subtraction method. This operation is effective in increasing and distilling Gaussian entanglement between quantum states, and can be easily realized by existing technology. Simulation results show that the channel-loss tolerance of the eight-state continuous variable quantum key distribution (CVQKD) protocol can be extended by the appropriate photon subtraction algorithm; namely, single-photon subtraction.